Presentations for The E-FooD Dataset and Food Security Simulators for Kenya and Nigeria: Innovative Tools to Support National Policies and Strategies - Ecker, Olivier; Comstock, Andrew R.; Mbuthia, Juneweenex; Momanyi, Dorah; Adeyemo, Temitayo (2023)
Recent global food price spikes and household income losses pose significant challenges to people’s food security and diets, raising important questions for governments and international organizations about how best to support households. The new Income and Price Elasticities of Food Demand (E-FooD) dataset [https://doi.org/10.7910/DVN/OXZ0H6] and Food Security Simulators (FSS) provide rigorous, yet easy-to-use tools for forward-looking evaluations of direct, household-level outcomes of economic crisis and policy responses. This webinar, organized by the CGIAR Initiative on National Policies and Strategies (NPS), introduces the E-FooD dataset and FSS for Kenya [https://doi.org/10.7910/DVN/NS1A7V] and Nigeria [https://doi.org/10.7910/DVN/WWMN6H], showcases their applications, and discusses the role that such tools can play in policymaking.